Kinetic and kinematic characteristics of sprint running with a weighted vest - Gleadhill, S.; Yuk, N.; Wada, T.; Nagahara, R. (Journal of Biomechanics, 2021)
This study elucidated kinetic and kinematic changes between control and weighted vest sprinting with a load of 7% body mass. Fourteen male sprinters completed 60 m control and vest sprints over a long force platform system. Step-to-step ground reaction force and spatiotemporal variables were grouped, representing the initial acceleration (1st-4th steps), middle acceleration (5th-14th steps), later acceleration (15th step-step before maximum velocity reached) and maximum velocity (stride where maximum velocity reached) phase during each trial. Two-way ANOVA with post hoc Tukey HSD and a Cohen`s d effect size with 95% confidence intervals elucidated the difference between trials and phases. Between control and vest trials the velocity decreased (3.41-3.78%) through trivial-small step length (1.95-2.72%) and frequency (0.87-1.54%) decreases. Vertical impulse increased (6.46-6.78%) through moderate support time increases (4.84-6.00%), coupled with no effective vertical mean force differences during the vest trial, compared to the control. There was no significant interaction between trials and phases. Therefore, although weighted vest trials did not increase vertical mean force production, vests did induce an increased vertical force application duration during the support phase step-to-step while supporting a larger total load (body mass plus vest mass).